The Effect of Vitamin D Supplementation on Glycemic Control and Cardiovascular Risk Factors in Type 2 Diabetes: An Updated Systematic Review and Meta-Analysis of Clinical Trials - Maryam Afraie; Pourya Bahrami; Parisa Kohnepoushi; Sorour Khateri; Lobat Majidi; Lotfollah Saed; Kamran Zamani; Hedyeh Mohammadi Baharm; Yousef Moradi; Farhad Moradpour (Journal of Diabetes Research)
Conclusion: The results also indicated that taking vitamin D supplements in the amount of 50,000 IU had a significant effect on reducing the indicators related to diabetes control. Based on the combined evidence, the findings of this meta-analysis suggest that vitamin D supplementation can significantly improve glycemic control and reduce the risk of complications associated with T2DM, especially cardiovascular diseases (CVDs).